Stewart–Bluefarb syndrome: Report of five cases and a review of literature. (September 2015) - Parsi, K; O'Connor, AA; Bester, L
Stewart–Bluefarb syndrome is a rare angioproliferative disorder characterised by acroangiodermatitis associated with an underlying arteriovenous shunt. This condition should be differentiated from acroangiodermatitis of Mali classically described in association with chronic venous insufficiency. Patients with Stewart–Bluefarb syndrome typically present with lower leg pigmented macules, papules and plaques that can coalesce to form larger confluent patches of pigmentation. Recognition of Stewart–Bluefarb syndrome may be difficult or delayed as the cutaneous manifestations may resemble a variety of other dermatological conditions. Most commonly, acroangiodermatitis may be confused with Kaposi's sarcoma and the condition is often referred to as 'Pseudo-Kaposi's sarcoma'. Acroangiodermatitis may also resemble or coexist with pigmentation of chronic venous insufficiency. As seen in this report, acroangiodermatitis may also be clinically confused with the 'cavernous' form of a capillary malformation. Here, we describe five patients with Stewart–Bluefarb syndrome. In one female and two male patients the diagnosis was delayed as the acroangiodermatitis closely resembled other conditions. All underlying arterio-venous communications were initially diagnosed on duplex ultrasound and confirmed with magnetic resonance angiography. Four patients were found to have a congenital arterio-venous malformation while one was diagnosed with a post-thrombotic arterio-venous fistula. Management included observation and intervention using a variety of techniques including percutaneous or trans-catheter embolisation, endovenous laser, radiofrequency ablation and foam ultrasound guided sclerotherapy. This case series highlights the challenges involved in the diagnosis and management of Stewart–Bluefarb syndrome. Given the local and systemic sequelae of high flow shunts, correct diagnosis and early detection of the underlying arterio-venous abnormality is crucial in the long-term management of these patients and in preventing the associated complications.